Bird Diversity in the Freshwater Swamp of Lake Tangkas Ecosystem, Sekernan District, Muaro Jambi Regency - Nursanti, Nursanti; Hutasoit, Monica Hazelina; Adriadi, Ade (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
After Colombia, Peru, and Brazil, Indonesia is the fourth richest country in the world in terms of the number of bird species. Lake Tangkas Nature TourismÂ is located in two administrative areas, namely Tanjung Terus Village, Sekernan District, Muaro Jambi Regency, and Desa Kaos, Pemayung District, Batanghari Regency, and has an extended form. The region surrounding Tangkas Lake, which is still in its original state, is an ideal habitat for bird species that nest. This study seeks to identify bird species inhabiting freshwater swamp habitats in the Muaro Jambi Tangkas Lake Natural Tourism destination region. This study was conducted in March 2021 at the Lake Tangkas Nature Tourist Area, Tanjung Terus Village, which has 403.11 hectares, Sekernan District, Muaro Jambi Regency. Collecting data on bird species using the point count method. Thirteen observation stations are employed as study locations as counting points. Observations were conducted during peak bird activity, namely in the morning from 6:00 to 10:00 WIB and in the afternoon from 14:00 to 18:00 WIB. According to the results of the study, 36 species of birds from 18 groups (475 individuals) were discovered in the freshwater swamp habitat of Tangkas Lake; the diversity index value is (H'=3.12). The evenness index is 0.87, which places the distribution of bird species in the studied area in the "high" category